Optimizing swirl in compact uniflow cyclones - Pillei, Martin; Kofler, Tobias; Wierschem, Andreas; Kraxner, Michael (Aiche Journal, 2019)
This paper presents an experimental examination of the velocity field distribution in the separation chamber of a uniflow cyclone with closed particle outlet to evaluate the swirl characteristics in the vortex finder region based on stereoscopic particle image velocimetry. A cold flow model with a closed particle outlet was used to assess different angles of attack and core size ratios at typical Reynolds numbers for the separation of low loaded gas-solid flows. The focus of the study was on the relationship between swirl strength as well as performance data. At higher angles, the parabolic swirl strength distribution changed to a region with constant high acceleration of the particles in the separation zone. Integral and differential swirl numbers were correlated with the ratio of tangential to radial velocity and to the calculated cut size diameter. At low angles of attack, implying a strong redirection of flow perpendicular toward the main flow direction and small core size ratios, defined by the radial distance between hub and tip, the local differential swirl number can be more than twice as large as in the base configuration. Yet, the integral swirl number hardly changed. The velocity fields showed mean tangential to radial velocity ratios ranging from 0.73 to 6.85 at swirl vane angles of 15 core size ratios between 0.125 and 0.625 at vortex finder diameter were measured and calculated cut size diameters between 10 and 90m were derived. This data provides the foundation for further validation studies and the development of new design criteria. (c) 2018 American Institute of Chemical Engineers AIChE J, 65: 766-776, 2019
CRIS-Team WoS Importer:2019-03-08